Marieta CANTOS CASENAVE (ed.), «Diccionario razonado... (Cádiz, 1811)», Sevilla, Renacimiento, 2021, 203 págs.; Bartolomé José GALLARDO, «Diccionario crítico-burlesco…», ed. de Alberto Romero Ferrer y Daniel Muñoz Sempere, Gijón, Ediciones Trea, 2022, 280 págs. - Durán López, Fernando (Cuadernos de Estudios del Siglo XVIII, 2022)
Sin resumen